2022
DOI: 10.1177/10600280211073936
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Versus Continuous Infusion Dosing of Intravenous Proton Pump Inhibitors for Upper Gastrointestinal Bleeding

Abstract: Background: Proton pump inhibitor (PPI) continuous infusions or intermittent boluses are used for the treatment of upper gastrointestinal bleeding (UGIB). Intermittent boluses are easier to give and are of lower cost without affecting clinical outcomes. Objective: To compare the rate of rebleeding between intermittent bolus and continuous infusion PPI therapy. Methods: We performed a retrospective, multicenter review of patients with UGIB receiving either continuous or intermittent PPI therapy. During the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Although the most recent guidelines advocate intermittent PPI medication, there is no agreement on which PPI agent, dose, or frequency should be used. 16 Our study also showed no significant difference in mortality rate between the intermittent and continuous PPI therapy groups (1 patient [1.7%] vs 3 patients [7.3%], p=0.308). Hsu et al 20 carried out a trial to compare 2 dosages of pantoprazole infusion for peptic ulcer bleeding.…”
supporting
confidence: 44%
See 3 more Smart Citations
“…Although the most recent guidelines advocate intermittent PPI medication, there is no agreement on which PPI agent, dose, or frequency should be used. 16 Our study also showed no significant difference in mortality rate between the intermittent and continuous PPI therapy groups (1 patient [1.7%] vs 3 patients [7.3%], p=0.308). Hsu et al 20 carried out a trial to compare 2 dosages of pantoprazole infusion for peptic ulcer bleeding.…”
supporting
confidence: 44%
“…There was also no change in the length of hospital or ICU stays, discharge disposition, or in-hospital mortality. 16 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PPI infusion administration was lacking with only 81% of patients receiving them despite evidence for the use of high‐dose PPI for 72 h to decrease the risk of rebleeding 12 . Although the intermittent intravenous infusion of proton pump inhibitors for UGIB is not associated with higher rates of bleeding, guidelines regarding a standardized bolus and continuous infusion would allow for standardized management of these patients providing a definitive resource for junior doctors initiating management, reducing uncertainty around medication administration, and thereby reducing the time to endoscopy 13 . Additionally, this would streamline clinical audits of these patients with specific treatment parameters.…”
Section: Discussionmentioning
confidence: 99%